2016
DOI: 10.1016/j.cattod.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of catalyst crystal structure on the oxidation of propene to acrolein

Abstract: Please cite this article in press as: Z. Zhai, et al., Effects of catalyst crystal structure on the oxidation of propene to acrolein, Catal. Today (2015), http://dx.a b s t r a c t Bismuth molybdate is known to be active for the oxidation of propene to acrolein and its activity can be altered by substitution of other elements (e.g. Fe, V, W) into the scheelite phase of ␣-Bi 2 Mo 3 O 12 . This work has further revealed that the apparent activation energy for acrolein formation correlates with the band gap of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 39 publications
1
30
1
Order By: Relevance
“…Kinetics study of propene oxidation on bismuth molybdate catalyst has reported that the rates of formation of the main product acrolein and byproducts CO and CO 2 are all nearly first order, corresponding to propene, and therefore the selectivity toward acrolein, CO, and CO 2 remains almost constant. 15,56 Since the selectivity of acrolein (85−90%) was observed to be significantly higher than those of acetaldehyde (0−5%) and CO x (5−10%), 12,15,17,28,29,56 therefore, the reaction rates of other by products (acetaldehyde and CO x ) are not mentioned in detailed in this study. The catalytic activity, instead, is expressed by the number of moles of acrolein formed per gram of catalyst (r w , mol/g•s) or per m 2 of surface area of the catalyst per second (r s , mol/m 2 •s) using the following formula: 1.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…Kinetics study of propene oxidation on bismuth molybdate catalyst has reported that the rates of formation of the main product acrolein and byproducts CO and CO 2 are all nearly first order, corresponding to propene, and therefore the selectivity toward acrolein, CO, and CO 2 remains almost constant. 15,56 Since the selectivity of acrolein (85−90%) was observed to be significantly higher than those of acetaldehyde (0−5%) and CO x (5−10%), 12,15,17,28,29,56 therefore, the reaction rates of other by products (acetaldehyde and CO x ) are not mentioned in detailed in this study. The catalytic activity, instead, is expressed by the number of moles of acrolein formed per gram of catalyst (r w , mol/g•s) or per m 2 of surface area of the catalyst per second (r s , mol/m 2 •s) using the following formula: 1.…”
Section: Methodsmentioning
confidence: 87%
“…54 Recent studies also reported linear correlations between the measured catalytic apparent activation energies for propene oxidation to acrolein and the band gap energies for several different families of multicomponent, mixed metal oxides. 55,56 Moreover, that band gap property, which correlates to the conductivity of the materials, 57 was also reported as an accurate descriptor for the energy to generate oxygen vacancy on metal oxides 58,59 and is very relevant for the incorporation of lattice oxygen into the reactant molecule. Therefore, those pieces of evidence further support our assumption that the conductivity could be one of the factors that reflect the catalytic activity in the oxidation of propene to acrolein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the band gap falls below 2.1 eV, the intrinsic selectivity to acrolein decreases rapidly and then decreases further with increasing propylene conversion. This pattern shows that when the activity of oxygen atoms at the catalyst surface becomes very high, two processes become more rapid-the oxidation of the intermediate from which acrolein is formed and the sequential combustion of acrolein to CO 2 [59].…”
Section: Bismuth -Advanced Applications and Defects Characterizationmentioning
confidence: 98%
“…Thus, the reaction occurs via a Mars and Van Krevelen mechanism in which propylene adsorbs reversibly and then reacts with an oxygen atom of the catalyst. This rate-limiting step leads to cleavage of one of the C-H bonds of the methyl group of the adsorbed propylene and results in the formation of an adsorbed OH group and a loosely adsorbed allyl radical that is rapidly stabilized as an adsorbed vinylalkoxide [59]. The sites for chemisorption and dissociation of gaseous oxygen molecule are spatially and structurally distinct from the active sites, at which adsorption and oxidation of propylene take places.…”
Section: Mechanism Of the Reactionmentioning
confidence: 99%